Instagram Feed to Teach Descriptive Writing - Nafita Santoso; Dina Kartikawati (LinguA-LiterA: Journal of English Language Teaching Learning and Literature, 2021)
The study aims to know about the effect between before and after taught using the Instagram feed. This study used pre-experimental with non-parametric. The researcher used one-group pre-test and post-test design. In this research, the population consists of grade tenth SMK Sore Tulungagung and 15 students in one class for the sample. The researcher used Cluster Sampling. The instruments used in this study were tests and Instagram feed. The analysis of the data obtained using Saphiro Wilk, Levene Test, and Wilcoxon Test in SPSS 21.0.  The finding of this research showed that the pre-test standard error mean is 0,235 < 5,40, and the post-test standard error mean is 0,133 < 8,47. The Asymp. Sig was 0,001, it was smaller than 0,05 (0,001 < 0,05). It can be concluded that the hypothesis is accepted. This means that there was a difference between the results of learning descriptive text writing for pre-test and post-test. Overall, it might be concluded that using Instagram as a teaching tool for writing the descriptive text was a good idea. Teaching writing descriptive text using Instagram Feed was effective for students at tenth-grade SMK Sore Tulungagung for the 2020/2021 academic year